2013
DOI: 10.11646/zootaxa.3619.1.6
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Chrysomelid males with enlarged mandibles: three new species and a review of occurrence in the family (Coleoptera: Chrysomelidae)</strong>

Abstract: Three new species of Chrysomelidae with extraordinary extensions of the male mandibles are described: Male mandible enlargment in the Chrysomelidae is reviewed: it is common in Cryptocephalinae, but otherwise restricted to a few species of Chrysomelinae, Eumolpinae and Galerucinae. Possible reasons for its distribution in the Chrysomelidae are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…This could explain why mandibles of N. upiformis are scoop-shaped. Besides, in chrysomelid beetles, it has been suggested that enlarged mandibles might be used by males as clasping organs during copulation [16]. It could also be the case for the curved mandibles of male N. upiformis but direct observation of their mating behaviour is needed to confirm such hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…This could explain why mandibles of N. upiformis are scoop-shaped. Besides, in chrysomelid beetles, it has been suggested that enlarged mandibles might be used by males as clasping organs during copulation [16]. It could also be the case for the curved mandibles of male N. upiformis but direct observation of their mating behaviour is needed to confirm such hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Spilopyrinae es una subfamilia pequeña, con distribución de tipo gondwánica, que sólo incluye nueve géneros con especies repartidas en Argentina, Australia, Chile, Nueva Caledonia y Nueva Guinea; a nivel mundial se reconocen 40 especies (Elgueta et al 2014, Jolivet et al 2014b, Reid 1992y 2000, Reid y Beatson 2010a-b, 2011y 2013, Verma y Jolivet 2002. Eumolpinae en cambio, con más de 500 géneros y cerca de 7.000 especies, es una subfamilia con representantes en prácticamente todas las regiones del mundo (ausente sólo en unas pocas áreas continentales e insulares), estando especialmente diversificada en las zonas tropicales (Jolivet y Verma 2008, Jolivet et al 2014a, Verma y Jolivet 2004.…”
Section: Introductionunclassified